MENEGUHKAN KEMBALI NILAI-NILAI PANCASILA DALAM KONTEKS KEKINIAN - Taufik, Cevi M; Haryani, Heni (LEMBAGA PUSAT KAJIAN KEBANGSAAN/PUSKAB UKRI, 2023)
The national spirit must always live on in all phases of era development. Its importance is not merely to emphasize national identity, but as the most essential manifestation of Indonesianness. It is inconceivable that if the national identity is lost and replaced by foreign values, then gradually the characteristics of Indonesia will be lost or at least will not have a character that shows its identity in world relations. In reality, the tendency in this direction is getting stronger amidst the influx of foreign culture which permanently intrudes into all sectors of life. This includes the struggle for values brought by foreign nations as well as the agenda of world nations who are trying to become a force to subdue other nations. Also unavoidable is the power of the cronies of the superpowers who are only oriented towards business and profit without recognizing the boundaries of nationalism. Facing conditions like this, national awareness must always be fostered and become a source of pride and directed in the form of internalizing values within every member of the nation. In this regard, the study was structured as an effort within the framework of bringing national values to life. Through the method of observing developments in the national situation, literature studies adapted from materials spread across various internet networks are strengthened as data that strengthens the analysis. The result is that national values must be embedded in every citizen of the nation with the practice of the principles of Pancasila as the strengthening basis that unites Indonesia.Â